2013
DOI: 10.5861/ijrsp.2013.339
|View full text |Cite
|
Sign up to set email alerts
|

Role of trust in marital satisfaction among single and dual-career couples

Abstract: The present study examined the role of trust in marital satisfaction in a sample of 140 couples including 70 single & 70 dual-career couples. Moreover, gender differences were also studied.Enrich Marital Satisfaction Scale (Fowers & Olson, 1993), and Trust Scale (Rempel, Holmes & Zanna, 1985) were used to measure the constructs. The age of the sample ranged from 25 to 61 years (M = 40.90, SD = 9.62). Multiple regression analysis demonstrated trust as significant predictor of marital satisfaction for single car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…The current study was carried out to translate and validate the TCRS for Pakistani married couples. TRCS was translated validated for married couples in the present study, because it has been reported that TRCS has wide application in close interpersonal relationship (Asif & Saim, 2018;Atta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study was carried out to translate and validate the TCRS for Pakistani married couples. TRCS was translated validated for married couples in the present study, because it has been reported that TRCS has wide application in close interpersonal relationship (Asif & Saim, 2018;Atta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the scale had been used in Pakistan for example by Atta et al (2013) but no documented evidence was found on the translation and validation of TCRS and the author also confirmed via e-mail that he had not received any details from the researchers in Pakistan on Urdu translation and validation of the scale. As the scale was originally developed in English, so in order to use TRCS in Pakistan for research on trust in marital commitment, researchers need a valid and reliable Urdu version of the scale to measure mutual trust in married couples.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Artinya variabel trust secara simultan berpengaruh signifikan pada variabel kepuasan pernikahan Berdasarkan uji analisis regresi yang telah dilakukan, menjelaskan bahwa semakin tinggi tingkat trust yang dimiliki individu, maka semakin tinggi pula tingkat kepuasan pernikahan, dan trust dapat menjadi prediktor untuk tingkat kepuasan pernikahan individu yang bertemu pasangannya melalui aplikasi online dan sedang menjalani pernikahan jarak jauh. Hasil penelitian ini sejalan dengan beberapa penelitian yang membahas mengenai pengaruh trust terhadap kepuasan pernikahan, antara lain penelitian dari Atta [18] yang bertujuan melihat peran trust terhadap kepuasan pernikahan pada pasangan menikah yang keduanya bekerja, dan juga yang hanya salah satunya saja yang bekerja. Lalu penelitian Arora & Shetgovekar [19] ingin membandingkan apakah trust berpengaruh pada kepuasan pernikahan pada pasangan menikah yang dijodohkan dengan atas dasar cinta.…”
Section: Pengaruh Trust (X) Terhadap Kepuasan Pernikahan (Y)unclassified
“…As per this study the factor for marital satisfaction varies from the view of husband and wife. 5,12,13 Potential factors affecting marital satisfaction as reported by researchers worldwide includePersonality type, 14 Religiocity, 15 Emotional stability, 16 Psychological factors i.e, depression, affection, sexual activities and Social factors i.e, number of children, communication, time spent together, 17 Single and dual-career, 18 Earning, 19 Husband attachment style, 20 Extramarital affairs, 21 Partner job and education. 22 Marital Satisfaction Scale (MSS) can be used to examine how marital satisfaction affects couples well-being.…”
mentioning
confidence: 99%